Efficient Multidimensional Pipelined Chaotic Bulk-Codewords-Encryption for Cloud Control Systems - Ali, Yasir; Manzoor, Tayyab; Yang, Huan; You, Lijie; Ma, Ruifeng; Yan, Chenhang; Wang, Taiqi; Xia, Yuanqing (IEEE transactions on cybernetics, 2025)
Cloud control systems (CCSs) are evolving rapidly, requiring secure communication channels to protect critical remote control tasks. This article introduces an efficient encryption mechanism configured for securing the physical layer communication in these systems while transmitting data over optical fiber networks using orthogonal frequency division multiplexing active optical networks. The proposed scheme takes advantage of the hypersensitive chaotic properties of the Lorenz map to provide robust multidimensional encryption and confidentiality. The encryption process involves arranging bulk encoded codewords in a table structure shape, with each column representing individual codewords encoded by pipelined successive cancellation polar encoding. A Lorenz map is then utilized to generate three distinct chaotic keys, which are employed to reindex the rows and columns of the table structured codeword along with the subcarrier remapping in the constellation map. This reindexing operation provides an additional layer of security against potential brute-force attacks. Performance metrics such as computational efficiency, security robustness, and resistance to various noise and distortion sources are being evaluated. The experimental results demonstrate promising levels of security and resilience against potential threats on the physical layer of communications. The scheme's compatibility with the technical environment ensures seamless integration into existing CCSs infrastructure, making it a resilient solution for securing critical physical layer transmissions.